Sorting out change - Brecht, Grant (Sorting out series, 1997)
This work covers such areas as: developing an attraction to change where possible; understanding why we allow change to bother us; being aware of the barriers to effective coping as one passes through the stages of dealing with change; and developing effective coping strategies.